Internet of Medical Things (IoMT): Applications and Challenges (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The Internet of Medical Things (IoMT) is revolutionizing healthcare by enabling remote patient monitoring, telemedicine, smart healthcare devices, and health data analytics. This paper provides a comprehensive review of the applications, benefits, challenges, and future trends of IoMT in healthcare. The applications of IoMT, including remote patient monitoring and telemedicine, have the potential to improve patient outcomes, enhance healthcare efficiency, and reduce costs. However, the implementation of IoMT is hindered by security and privacy concerns, interoperability issues, regulatory challenges, and data management complexities. Future trends of IoMT, such as the integration of artificial intelligence and machine learning, blockchain technology, IoMT ecosystem integration, and personalized medicine, promise to further enhance its capabilities and impact in healthcare. By addressing these challenges and embracing these trends, healthcare organizations can harness the full potential of IoMT to create a more connected, efficient, and patient-centric healthcare system.